Foreign Direct Investment, Trade Credit, and Transmission of Global Liquidity Shocks: Evidence from Chinese Manufacturing Firms - Lin, Shu; Ye, Haichun (Review of Financial Studies, 2018)
We empirically explore a trade credit channel through which foreign direct investment (FDI) firms can propagate global liquidity shocks to the host country despite its tight controls on portfolio flows. In a large sample of Chinese manufacturing firms, we find robust evidence that FDI firms provide more trade credit than local firms during tight domestic credit periods and that a favorable global liquidity shock amplifies FDI firms’ advantage in trade credit provision. Moreover, the differential responses of FDI and local firms are stronger in financially more dependent industries or in Chinese provinces with less financial depth. Received August 12, 2016; editorial decision May 16, 2017 by Editor David Denis.